HUBUNGAN BEBAN KERJA DAN KELELAHAN KERJA PADA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT SANTA ELISABETH MEDAN - Ance M Siallagan (ITKES Wiyata Husada Samarinda, 2022)
Fatigue is a normal body response experienced by a person and has an impact on oneself in carrying out activities or tasks and responsibilities that must be completed within a certain time. Work fatigue in nurses occurs due to workload factors, the level of patient dependence and hospital management. This study aims to identify the relationship between workload and work fatigue on nurses in the inpatient room at Santa Elisabeth Hospital Medan. This study used a descriptive correlative design with a cross sectional approach to all 109 nurses in the inpatient room. The results obtained in this study illustrate that the workload of 62.4% nurses is included in the light category and 50.5% of nurses experience work fatigue. The results of the chi-square statistical test obtained p-value = 0.35 (p>0.05) which means that there is no relationship between workload and work fatigue in inpatient nurses at Santa Elisabeth Hospital Medan. Future researchers are expected to identify other factors that cause work fatigue in nurses, both inpatient and special care such as emergency units and intensive care.